Direct power control for DFIG systems under distorted voltage using predictive repetitive control - A. Lunardi; E.R. Conde; N. Rocha; A.J. Sguarezi Filho (International Journal of Electrical Power & Energy Systems)
This paper presents the project of direct predictive repetitive power control for DFIG applied to the electrical grid in the presence of harmonic elements. The expanded model for the controller project proposed in this article is obtained through the mathematical model of the generator in state space with the active and reactive power as a state. The controller is implemented on an experimental bench, where the obtained results are presented to support the controller’s efficiency and ability to reject disturbances. The disturbances are mitigate due to the addition of a polynomial that includes an integrative effect on the plant in its expanded model. Results with regular operation and distorted voltage are essential to show the performance of the direct repetitive predictive power controller. Finally, from the results, the conclusions discuss the most critical characteristics to validate the proposed controller.